Biological therapy in psoriasis treatment - Woźniak, Marta; Nowicki, Roman (Przewodnik Lekarza/Guide for GPs, 2005)
Psoriasis is a chronic, immune-mediated disorder that usually requires long-term treatment for control. Despite the availability of numerous therapeutic options, the long-term systemic management of psoriasis can be complicated by numerous adverse reactions. Biological therapies are designed to modulate key steps in the pathogenesis of psoriasis. Biologicals have demonstrated significant benefit with favou- rable safety and tolerability profiles.